Philosophical explication of culture in the works of V. Ivanov and A. Yatsenko - V. E. Turenko; N. V. Yarmolitska (Ukrainian Cultural Studies, 2020)
The article attempts to highlight the understanding of culture in the work of famous Ukrainian Soviet philosophers of the second half of the ХХ century – Vadym Ivanov and Olexandr Yatsenko. Ukrainian Soviet philosophy of the postwar period is known primarily for research in logic, philosophical problems of science, philosophical anthropology, as well as research on the history of national philosophy. At the same time, philosophical and cultural issues seemed to be "in the shadow" of the above studies and actually leveled off in this period of development of Ukrainian philosophical thought. Because of this, there is a need to analyze the legacy of Ukrainian Soviet philosophers, who focused their attention on the philosophical explication of the phenomenon of culture. V. Ivanov and O. Yatsenko were among such thinkers. The thesis is substantiated that the philosophical comprehension of culture, of course, was not in the center of attention of the studied Ukrainian thinkers, however, while developing these or those concepts, they certainly concerned reflections on the cultural phenomenon, which became important for the development of the philosophical tradition in Ukraine. It is proved that for V. Ivanov culture becomes one of the most important factors of human self-realization and self-realization. It is especially important to emphasize that the culture of the Ukrainian Soviet philosopher is very connected with various kinds of social phenomena, thereby making it key in interpersonal relations in society. V. Ivanov emphasizes that culture is not a system, but one of the elements of human existence and manifestation of its existence. Thus, culture in the context of human existence determines not only the present, but also the perspective on which human progress is directed in one aspect or another. It was revealed that O. Yatsenko notes the close interconnection of culture and goal setting and ideals. In his opinion, culture, being a social phenomenon, is one of the key forms in which a person is able to realize his goals and ideals.